Pengaruh Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan CV Aneka Grafika Malang - Ummi Khusnul Chotimah; Erna Resmiatini (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2024)
This research aims to determine and analyze the influence of leadership and work discipline on the performance of CV Aneka Graphics Malang employees. The population of this research is 158 CV Aneka Graphics Malang employees, using a sample of 62 respondents. The sampling technique uses random sampling technique. The research methods used are quantitative methods and questionnaires for collecting data directly from respondents. Data analysis techniques in this research are using validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple regression analysis and hypothesis testing (t test, F test, and coefficient of determination test). The research results show that partially leadership has no significant effect on employee performance while work discipline has a significant effect on employee performance. Meanwhile, leadership and work discipline simultaneously have a significant effect on employee performance